EFEKTIVITAS SICANTIK CLOUD PADA PELAYANAN PUBLIK PERIZINAN BERBASIS E- GOVERMENT DIKABUPATEN PURWAKARTA - Nurrahman, Agung; Rahman, Jamilah (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2021)
The focus of the study is the application of the Si Cantik Cloud application. The purpose of this study is to obtain a general description of the effectiveness of Si Cantik in e-government-based licensing public services in Purwakarta Regency. The research method is descriptive qualitative. The research findings indicate that there are supporting factors, namely the commitment of organizational leaders in this case as illustrated in the publication of SOPs supporting the implementation of the Si Cantik Cloud application which can have implications for clarity of information for the business community. In conclusion, on the 5 dimensions used by the author in measuring effectiveness, information is obtained that the Si Cantik Cloud application implemented by the Purwakarta Regency Investment and One Stop Integrated Service (DPMPTSP) shows that the application is quite effective in being used and utilized in the provision of licensing and non-licensing services in Indonesia. Purwakarta Regency. The author recommends that the Purwakarta Regency Government can improve socialization and assistance to the community, and develop infrastructure designs in order to strengthen the effectiveness of implementing the Si Cantik Cloud application. Keywords: Effectiveness, Si Cantik Cloud, Public Service, E-government.